Analysis Acceptance of Academic System Using TAM and DeLone & McLean (D&M ISSM) - Hanifa Huzaima (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
SIAK is an academic information system that has been implemented since 2018. Users of the SIAK system are active students, while in its implementation SIAK experiences several obstacles such as some menus available there are SIAK services in its application are considered ineffective, such as the forgot password menu that cannot be used, but the system is not user-friendly. The obstacles experienced will affect the acceptance of SIAK users. The main objective of the study is to ascertain how SIAK consumers feel about the service. The modified TAM model includes, perceived usability, ease and acceptance, information quality variables, system quality, and service quality of Delone and Mclean ISSM models. Using the Slovin formula and sampling techniques using Simple Random Sampling, this research obtained one hundred students as research samples. SmartPLS V 3.0 for PLS-SEM data processing. Of the 8 hypotheses given, 7 were approved, and 1 was the rejected variable is Service Quality which does not show a positive relationship with the Perceived Ease of Use